Mathematics Anxiety’s Impact on Grade 11 General Mathematics Performance - Moroscallo , Teodoro Jr (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the relationship between math anxiety levels and the academic performance of Grade 11 students in General Mathematics. Utilizing a descriptive-correlational design, the research aims to delineate the profile of respondents concerning their math anxiety levels and academic performance. The sample comprised forty-nine Grade 11 students. The primary research instrument was Ellen Freedman’s standardized Self-Test for Math Anxiety. Findings indicate that the respondents exhibited moderate levels of math anxiety and their academic performance in General Mathematics was generally satisfactory. Notably, a significant relationship was found between math anxiety and the respondent's sex. Additionally, the study revealed a negative correlation between math anxiety and academic performance, indicating that higher levels of math anxiety are associated with poorer academic performance in General Mathematics, and conversely, lower levels of math anxiety correlate with better academic performance. The study concludes with recommendations for educational practice and suggestions for future research directions.